The Influence of User Experience (UX) and Customer Experience (CX) on Purchasing Decision - Alghifari Akbar Budiono; Alamsyah, Indra Fajar; Meirani, Nadia (UNISBA Press, 2024)
Abstract. This research focuses on the variables of User Experience (UX), Customer Experience (CX) and Purchasing Decision. This study aims to test and determine the effect of User Experience (UX) and Customer Experience (CX), Purchasing Decision on Apple IPhone users and customers in Sukabumi City. This research is included in the type of descriptive and verification research with quantitative methods. The sampling technique used was random sampling. The data collection method used in this study is a survey method with a questionnaire instrument. The object of this research is Apple IPhone users and customers in Sukabumi City and have owned an Apple IPhone in the last 6 months or 1 year with a total of 93 respondents. The data analysis used is descriptive and verification analysis, namely by using multiple linear regression analysis, F test, t test and coefficient of determination. The results of this study indicate that User Experience (UX) partially has a positive and significant effect on Purchasing Decision, Customer Experience (CX) has a positive and significant effect on Purchasing Decision. Then simultaneously User Experience (UX) and Customer Experience (CX) have a positive effect and on Purchasing Decision. With a good User Experience and Customer Experience (CX), it is expected that it will provide Purchasing Decision to achieve better results. Abstrak. Penelitian ini berfokus pada variabel Pengalaman Pengguna (User Experience/UX), Pengalaman Pelanggan (Customer Experience/CX), dan Keputusan Pembelian. Tujuan penelitian ini adalah untuk menguji dan menentukan pengaruh Pengalaman Pengguna (UX) dan Pengalaman Pelanggan (CX) terhadap Keputusan Pembelian pada pengguna dan pelanggan Apple iPhone di Kota Sukabumi. Penelitian ini termasuk dalam jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik pengambilan sampel yang digunakan adalah random sampling. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode survei dengan instrumen kuesioner. Objek penelitian ini adalah pengguna dan pelanggan Apple iPhone di Kota Sukabumi yang telah memiliki Apple iPhone dalam 6 bulan terakhir atau 1 tahun dengan total 93 responden. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif, yaitu dengan menggunakan analisis regresi linier berganda, uji F, uji t, dan koefisien determinasi. Hasil penelitian ini menunjukkan bahwa Pengalaman Pengguna (UX) secara parsial berpengaruh positif dan signifikan terhadap Keputusan Pembelian, Pengalaman Pelanggan (CX) juga berpengaruh positif dan signifikan terhadap Keputusan Pembelian. Secara simultan, Pengalaman Pengguna (UX) dan Pengalaman Pelanggan (CX) berpengaruh positif terhadap Keputusan Pembelian. Dengan Pengalaman Pengguna dan Pengalaman Pelanggan yang baik, diharapkan dapat meningkatkan Keputusan Pembelian untuk mencapai hasil yang lebih baik.